The impact of free and fair parliamentary elections on the legitimacy of governments (Kurdistan Regional Parliament elections as a model) - Zana Jalal Saeed; Ameen Faraj Sharif; Dana Abdulkarim Saeed (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Elections are one of the most basic means of enjoying the right to political participation, which can contribute to the building of constitutional institutions, the legitimization of political power, the realization of the meaning of peaceful and periodic circulation, the expansion of political participation and the empowerment of citizens to express their opinions and other functions. Although elections are an essential condition of the parliamentary system of government, they are not sufficient to describe the system as democratic. Some researchers have set a series of procedures, standards and safeguards that define democratic elections to differentiate them from electoral mechanisms in undemocratic regimes. The practical importance of the study is that it is an attempt to assess the experience of the Kurdistan Region, in terms of the extent of compliance with the standards of freedom and integrity of the parliamentary elections held since 1992. The basic premise of the study is a statement of opinion that if this means to achieve its objectives and be truly reflective of the hopes and aspirations of the people, it must be free and fair. As for the experience of the Kurdistan Region, we believe that it has applied certain criteria of freedom of elections in parliamentary elections, with many shortcomings and gaps. The research consists of three sections, the first subject deals with the importance of the elections as a criterion for the legitimacy of governments. In the second part, we discussed the most important criteria for freedom of elections. The third and final topic dealt with the evaluation of the parliamentary elections held in the Kurdistan Region.